Pengaruh Kualitas Produk, Harga, dan Kualitas Pelayanan Terhadap Keputusan Pembelian dengan Kepuasan Konsumen Sebagai Variabel Intervening pada Nilna Mukena Ngunut Tulungagung - Dewi Anggun Novitasari; Ali Mauludi AC (Universitas Batanghari, 2023)
Competition in the business world is increasingly competitive, so business people are required to continue to innovate and provide the best products and services in winning business competition. Nilna Mukena is a business that produces mukena with various models in Ngunut Tulungagung. Nilna Mukena must pay attention to customer satisfaction, because this is one of the successes in a business and encourages consumers to make purchasing decisions. Factors that influence consumer purchasing decisions include product quality, price, service quality, and customer satisfaction. The objectives of this study were 1) to measure the direct and indirect effects of product quality, price, and service quality on purchasing decisions with customer satisfaction as an intervening variable, and 2) to determine the total amount of each variable effect of product quality, price, and service quality on Nilna Mukena. This research approach is quantitative. This type of research is comparative causal. The data analysis technique of this research is multiple linear regression. Comparative causal research is research that compares which is the stronger direct or indirect effect of each independent variable on the dependent variable and compares the total amount of influence of each independent variable. The population of this study were Nilna Mukena consumers and the number was unknown. The sample used was 100 respondents. The sampling method is by filling out a questionnaire distributed to consumers who come to Nilna Mukena. The test results in this study indicate that product quality has no effect on customer satisfaction, product quality has no effect on purchasing decisions, price has a significant positive effect on customer satisfaction, price has no effect on purchasing decisions, service quality has a significant positive effect on customer satisfaction, service quality has a significant positive effect on purchasing decisions, customer satisfaction has a significant positive effect on purchasing decisions, customer satisfaction provides a role in mediating prices on purchasing decisions, customer satisfaction does not provide a role in mediating product quality and service quality on purchasing decisions at Nilna Mukena Ngunut Tulungagung.